2009
DOI: 10.1292/jvms.71.645
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of the Canine Fragile Histidine Triad (FHIT) Gene and Fhit Protein Expression in Canine Peripheral Blood Mononuclear Cells

Abstract: ABSTRACT. A fragile histidine triad (FHIT) gene has been studied as a tumor-associated gene in humans. The aberrant FHIT gene and its protein expression have been reported in many types of human cancers. The present study explored the canine FHIT gene structure and its protein expression in the peripheral blood mononuclear cells of healthy dogs by RT-PCR, RACE and immunoblot analysis. The obtained canine FHIT gene contained nine small exons and was located on canine chromosome 20. Furthermore, we identified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…We prepared 3 primer pairs-e1/eL, BF1/eL and TF5/TF3 (Table 1)-to detect the canine FHIT genes; in our previous study, we had confirmed that these 3 primer pairs amplify the canine FHIT gene transcripts [15]. These primer pairs were used to amplify exons 1 to 9 of the canine wild-type FHIT transcript, exons 3B to 9 of the alternative splicing form (type B), and exons 4 to 8 of the common ORF of these transcripts (Fig.…”
Section: Cellsmentioning
confidence: 89%
See 4 more Smart Citations
“…We prepared 3 primer pairs-e1/eL, BF1/eL and TF5/TF3 (Table 1)-to detect the canine FHIT genes; in our previous study, we had confirmed that these 3 primer pairs amplify the canine FHIT gene transcripts [15]. These primer pairs were used to amplify exons 1 to 9 of the canine wild-type FHIT transcript, exons 3B to 9 of the alternative splicing form (type B), and exons 4 to 8 of the common ORF of these transcripts (Fig.…”
Section: Cellsmentioning
confidence: 89%
“…It has recently been shown that an alternative splicing form-the type-B FHIT transcript-is coexpressed with the wild-type FHIT transcript in the PBMCs, spleen and intestine of healthy dogs and that it may play a role in an alternative Fhit-protein-expressing system that is activated when expression of the wild-type transcript is reduced [15]. In this study, the type-B transcript could not be detected in any of the canine lymphoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations